2018
DOI: 10.1016/j.ejvs.2018.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Single Stage Hybrid Repair for DeBakey Type I Aortic Dissection in High Risk Patients

Abstract: IAD was treated safely and durably by Z0 HAR, and peri-operative mortality and morbidity were not substantially higher despite the older age and high risk of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In our study, it was found that the short-term 30-day mortality rate and the long-term 1- and 3-year mortality rates of the two surgical methods were similar. In the recent studies of hybrid surgery, it was found that the in-hospital mortality rate of hybrid surgery for type A aortic dissection is about 6.0–9.2% ( 23 , 24 ), which is similar to the mortality rate of FET surgery. In addition, in the multivariate regression analysis of this study, the surgical method is not an independent predictor of short-term and long-term post-operative mortality.…”
Section: Discussionmentioning
confidence: 70%
“…In our study, it was found that the short-term 30-day mortality rate and the long-term 1- and 3-year mortality rates of the two surgical methods were similar. In the recent studies of hybrid surgery, it was found that the in-hospital mortality rate of hybrid surgery for type A aortic dissection is about 6.0–9.2% ( 23 , 24 ), which is similar to the mortality rate of FET surgery. In addition, in the multivariate regression analysis of this study, the surgical method is not an independent predictor of short-term and long-term post-operative mortality.…”
Section: Discussionmentioning
confidence: 70%
“…Composite primary endpoints for this analysis included peri-operative mortality, permanent neurological damage (paraplegia or stroke), and renal disorder necessitating hemodialysis upon release from hospitalization [ 17 ]. Secondary mid-term outcome endpoints included delayed death and a lack of need for delayed aortic reinterventions.…”
Section: Methodsmentioning
confidence: 99%
“…1 5 . LBM was determined with the James Composite primary endpoints for this analysis included peri-operative mortality, permanent neurological damage (paraplegia or stroke), and renal disorder necessitating hemodialysis upon release from hospitalization 17 . Secondary mid-term outcome endpoints included delayed death and a lack of need for delayed aortic reinterventions.…”
Section: Outcome Measuresmentioning
confidence: 99%